2014
DOI: 10.1111/let.12082
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy and habitat preference of North American pachycephalosaurids (Dinosauria, Ornithischia)

Abstract: The traditional view of North American pachycephalosaurids holds that their domes are typically worn, as though they had undergone extensive fluvial transport, and that these animals therefore inhabited upland environments (e.g. piedmont/intermontane settings) relative to where their remains are typically found. Using a statistically robust sample of domes from Alberta, Canada, we subject these hypotheses to various forms of quantitative testing and show that: (1) domes typically exhibit minimal rounding; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Yearling-sized juveniles had approximate total body lengths of 2.5 m, which was about a quarter of the size of the average adult from the DPF (∼9 m). This is similar in size with other penecontemporaneous smallto mid-sized ornithischian dinosaurs such as hypsilophodontids and pachycephalosaurids (Ryan and Evans 2005) that, based on analyses of vertebrate microfossil assemblages, preferentially lived in terrestrial inland paleoenvironments (Brinkman 1990;Baszio 1997;Brinkman et al 1998), although a taphonomic study of pachycephalosaurs suggested alluvial and coastal plain settings were similarly common (Mallon and Evans 2014).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Yearling-sized juveniles had approximate total body lengths of 2.5 m, which was about a quarter of the size of the average adult from the DPF (∼9 m). This is similar in size with other penecontemporaneous smallto mid-sized ornithischian dinosaurs such as hypsilophodontids and pachycephalosaurids (Ryan and Evans 2005) that, based on analyses of vertebrate microfossil assemblages, preferentially lived in terrestrial inland paleoenvironments (Brinkman 1990;Baszio 1997;Brinkman et al 1998), although a taphonomic study of pachycephalosaurs suggested alluvial and coastal plain settings were similarly common (Mallon and Evans 2014).…”
Section: Discussionsupporting
confidence: 68%
“…One explanation of this pattern is that the underrepresentation of yearlings is an artifact of taphonomic biases (e.g., hydraulic winnowing, predation) against the preservation of small-bodied skeletons in fluvial systems (Brown et al 2013a,b,c; Evans et al 2013; Mallon and Evans 2014). Given that nestling and 2-year-old individuals are well-represented in the DPF and TMF, it is difficult to imagine a taphonomic process that would selectively act against the preservation of yearlings or an intermediate size class between hatchlings and subadults.…”
Section: Discussionmentioning
confidence: 99%
“…A–D). Mallon & Evans () showed that the central dome of pachycephalosaur crania was the portion most commonly preserved, with less durable elements of the face and palate preferentially lost; based on recent collecting in Zambia and Tanzania, burnetiamorphs appear to show the same pattern (Sidor et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…These dinosaurs are easily characterised by the fusion and doming of the frontals and parietals (Maryańska et al 2004;Sullivan 2006). Dome morphology is taxonomically informative (although ontogenetically variable), and their high preservation potential (Evans et al 2013) make isolated domes a focus in pachycephalosaurid research (Sullivan 2003;Goodwin & Horner 2004;Sullivan 2006;Schott et al 2009;Lehman 2010;Longrich et al 2010;Schott et al 2011;Evans et al 2013;Mallon & Evans 2014;Schott & Evans 2016;Evans et al 2018).…”
Section: Introductionmentioning
confidence: 99%